Effective Technologies for Preparing Children with Disabilities for Social Life in Conditions of Inclusive Education - Usarov, Jabbor Eshbekovich; Kodirova, Feruzakhon Usmanovna; Akhlan, Riksma Nurahmi Rinalti (Angstrom Centre of Education, 2024)
This article describes how the level of formation of personal qualities in deaf, weak hearing children is determined not by hearing impairment, but in connection with acquired knowledge, skills, qualifications and life competencies through a complex of social influences.Through the foundational experimental and test work of the study, work aimed at preparing students for social life during the period of school education was established, professional competencies of educators, opportunities for students to receive information and transfer.